Effect of drought stress on indigo and seed yield of Indigofera tinctoria ecotypes - Rastegari, Faramarz; Tohidinejad, Enayatollah; Mohammadi-Nejad, Ghasem (The Indian Journal of Agricultural Sciences, 2020)
The objective of the the current study was to elucidate the effect of drought stress on indigo yield and to derive certain morphological traits of indigo ecotypes. This experiment was laid out in a split-plot arranged at a randomized complete block design, with three replications in the Jiroft Agricultural and Natural Resources Research and Education Center, Kerman, Iran, during 2013-14 growing seasons. The main plot and the subplot included drought stress (100, 75, and 50% of crop water requirement) and indigo ecotypes (Jiroft, Roudbar, Rigan, and Ghale Ganj), respectively. The obtained results showed that morphological and indigo content attributes revealed significant differences between the control and the drought-stress plants. Increasing water stress (up to 50% of crop water requirement) resulted in a severe loss of leaf dry mass, plant height, and seed yield of 25, 25 and 58%, respectively, in comparison to the control condition; the highest indigo yield and content obtained from the mid-stress level. Moreover, interaction effects of drought and ecotypes on leaf dry mass, seed, and indigo yield were significant; thus, the LDM and seed yield was the greatest in the Jiroft ecotype in the control, the indigo yield was the greatest under mid-level stress, and it was the lowest in the Ghale Ganj ecotype under severe water-stress level. Therefore, the results of this research suggest that the Jiroft ecotype will perform well with respect to drought tolerance and will be useful for cultivation in the semi-arid regions of Jiroft.